Femtosecond Laser Plane-by-Plane Inscribed Cavity Mirrors for Monolithic Fiber Lasers in Thulium-Doped Fiber - Theodosiou, Antreas; Aubrecht, Jan; Kašík, Ivan; Dousek, Daniel; Komanec, Matěj; Kalli, Kyriacos (Sensors (Basel, Switzerland), 2021)
A monolithic fiber laser operating in the short wavelength infrared that is suitable for CO2 gas sensing applications is proposed and presented. The current study reports a laser design based on the direct inscription of a monolithic Fabry-Perot (FP) cavity in a thulium-doped optical fiber using the femtosecond laser (FsL) plane-by-plane inscription method to produce the cavity mirrors. The FP cavity was inscribed directly into the active fiber using two wavelength-identical fiber Bragg gratings (FBGs), one with high and one with low reflectivity. Initially the effective length of the fiber was defined using a single high reflectivity FBG and subsequently a very weak FBG was inscribed at the other end of the fiber in order to demonstrate a fully monolithic fiber laser. All fiber lasers were designed for continuous wave operation at 1950 nm and characterized with respect to the power output, slope efficiency, stability, and effective resonator length. The performance of the presented monolithic laser cavities was evaluated using the same active fiber as a reference fiber spliced to FBGs inscribed in passive fiber; an improvement exceeding 12% slope efficiency is reported for the presented monolithic laser.
Keywords: monolithic fiber lasers; fiber lasers; fiber Bragg gratings; femtosecond laser